(untitled) (Lantanida Journal, 2020)
Bread is one type of food that is much in demand by the public because of its practical form and has various types of flavors, affordable prices and easy to get. To maintain bread more durable not easy to moldy and not easily damaged often added and abused preservatives such as borax. The research objective is to determine whether or not the borax content of commercial and traditional pillow bread in Blang Pidie District. The method used is qualitative with a flame test and color test using turmeric paper. The results showed that all traditional and commercial pillow breads using the flame test and color test methods of the 9 samples showed no positive results (+), meaning that none contained borax which was negative (-). Based on this study it can be concluded that, obtained in both the flame test and the color test on the content of borax on bread sold in Blang Pidie District all of the samples were negative (-) did not contain borax.